Dialysis Access Management - Wu, Steven; Kalva, Sanjeeva P. (Springer International Publishing : Imprint: Springer, 2015)
This practical book covers the basic principles and practice of dialysis access management, a crucial part of the care of patients undergoing hemodialysis. It has been written in an easy-to-read, step-by-step format to help facilitate learning and understanding of the procedures, and has been supplemented with numerous operative photographs and diagrams demonstrating the commonly performed dialysis access exams, interventions, procedures and surgeries. Dialysis Access Management is an essential text for residents, fellows, and physicians who are learning or practicing in dialysis and/or dialysis access management, especially in the fields of nephrology, radiology, surgery, and vascular medicine.